Microfacies of Mesozoic Carbonate Rocks of Slovenia - Ogorelec, Bojan (Geologija, 2011)
Carbonate rocks of Mesozoic age are widespread in Slovenia where they consitute about 40 % of its territory, and attaining total thickness of more than 5000 metres . With respect to microfacies almost all structure types can be recognized, the limestones and dolomites being formed in various sedimentary environments, such as in open and in restricted parts of carbonate shelf, in lagoons and on coastal plains, in different types of reefs, on slopes and in the basin. Carbonate sedimentation was often accompanied also by the supply of terrigenous material and products of volcanic activity. Among diagenetic processes in investigated carbonate rocks the most extensive are dolomitization and silicification. In the present text 250 microscopic photographs of characteristic limestones and dolomites from Slovenian territory are assembled. In the introductory part, to which for orientation schematic stratigraphic columns are added, the geologic development od these carbonate rocks is briefly outlined. For the sake of completeness in presenting the »carbonate era« in the overview, Upper Permian limestones and dolomites are also described next to Mesozoic beds.